Characteristics and experiences of peer counsellors in urban Dhaka: a structured interview study - Seema Mihrshahi; Hannah Tait; Rukhsana Haider; Gulshan Ara; Iqbal Kabir; Michael J. Dibley (BMC, 2019)
Abstract Background Interventions to promote breastfeeding are the cornerstone of efforts to reduce childhood illness and death from undernutrition. Evidence suggests that one of the most effective strategies to increase breastfeeding is through peer counsellors. However, the experiences of peer counsellors has not been studied in depth. This study aimed to collect and report the experiences of peer counsellors participating in an intervention study to improve breastfeeding in urban Dhaka, Bangladesh. Methods Peer counsellors underwent a 10 day training course in May 2013 which included practical sessions on position and attachment and common difficulties with breastfeeding. Home visits were conducted with new mothers and performance of peer counsellors was monitored by senior breastfeeding counsellors. The number of supervised home visits needed to achieve a satisfactory level of competency was recorded. Demographic data were collected and a structured interview was performed in the first six months of the project (May-September 2013). One structured interview per peer counsellor was conducted by the project manager at the project site office to gain understanding of their experiences in counselling mothers. The interview included some open-ended questions on specific aspects of the training that they found useful, challenges faced, and whether they developed close friendships with the mothers that they were counselling. Results Seventeen peer counsellors with an average age of 31 years (SD 6.8) and at least six years of schooling participated in the study. All peer counsellors were satisfied with their role and with the training that they received, and most felt that they were able to deal with common breastfeeding problems. The peer counsellors reported that building a personal rapport and establishing a peer-to-peer relationship was most important in supporting mothers to breastfeed. Common challenges included interruption of sessions by relatives/children, as well as mothers being too busy for the visits. Conclusion In future peer counselling for breastfeeding projects, more focus could be placed on the communications aspects of the training, especially in how to deal with non-supportive family members and managing interruptions effectively, as well as how to motivate and engage busy new mothers.